An Exploration of Key Issues in the Debate Between Classic and Constructivist Grounded Theory - Anne O’ Connor; Barry Carpenter; Barry Coughlan (Grounded Theory Review: An International Journal)
In this paper, the debates and discourse between Classic GT or Constructivist GT are explored. The aim of this paper is to evaluate the various claims in a critical manner by revisiting the original discourse outlining these approaches. The importance of maintaining a reflective, neutral stance while examining the arguments and evidence for the claims on both sides of this debate is emphasized. In the final analysis, the view taken by these researchers was that valid arguments could be made to support Classic and Constructive GT approaches. The rationale for choosing a Classic GT methodology is outlined. Guidelines to support novice researchers in their task of choosing the most appropriate GT approach are suggested.